The system of checks and balances in Colombia and political satire. - Ospina Celis, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
It is common to refer to the right to freedom of expression as the basis or underpinning of democracy; however, the implications of this assertion in constitutional theory are rarely analysed. This article argues that the constitutional protection of political satire is fundamental for the state and democracy, as it strengthens the mechanism of checks and balances, and the balance of powers, which in nations such as Colombia has not been consolidated. In this sense, starting from the classic formulation of the doctrine of the division of powers and its application in Latin America, the impact of political satire in the modern state will be analysed.